2023
DOI: 10.3389/fnut.2023.1176213
|View full text |Cite
|
Sign up to set email alerts
|

Maternal monosaccharide diets evoke cognitive, locomotor, and emotional disturbances in adolescent and young adult offspring rats

Abstract: Anxiety and depression are the most common mental disorders affecting people worldwide. Recent studies have highlighted that a maternal high-sugar diet (HSD) could be a risk factor for neurobehavioural dysregulations, including mood disorders. Increased consumption of added sugar in food such as refined fructose/glucose can increase the risk of metabolic disorders and impact susceptibility to mental disorders. Furthermore, a few papers have reported disabilities in learning and memory among offspring after mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
0
1
Order By: Relevance
“…This study also noted a decrease in climbing behavior in female offspring of mothers with a high fructose diet. In contrast to our findings, Witek et al (2023) reported that male rats were more susceptible to hyperactivity and anxiety-and depressive-like phenotypes than female rats, but this was observed during adolescence rather than early adulthood. It is possible that the changes occurring during adolescence could facilitate neuronal plasticity and reduce the prevalence of behaviors associated with depression and anxiety in the long term.…”
Section: Anxiety-related Behaviorcontrasting
confidence: 99%
“…This study also noted a decrease in climbing behavior in female offspring of mothers with a high fructose diet. In contrast to our findings, Witek et al (2023) reported that male rats were more susceptible to hyperactivity and anxiety-and depressive-like phenotypes than female rats, but this was observed during adolescence rather than early adulthood. It is possible that the changes occurring during adolescence could facilitate neuronal plasticity and reduce the prevalence of behaviors associated with depression and anxiety in the long term.…”
Section: Anxiety-related Behaviorcontrasting
confidence: 99%